The thermal ecology and physiology of reptiles and amphibians: A user's guide. Issue 1 (8th July 2020) - Taylor, Emily N.; Diele‐Viegas, Luisa M.; Gangloff, Eric J.; Hall, Joshua M.; Halpern, Bálint; Massey, Melanie D.; Rödder, Dennis; Rollinson, Njal; Spears, Sierra; Sun, Bao‐jun; Telemeco, Rory S.
Abstract: Research on the thermal ecology and physiology of free‐living organisms is accelerating as scientists and managers recognize the urgency of the global biodiversity crisis brought on by climate change. As ectotherms, temperature fundamentally affects most aspects of the lives of amphibians and reptiles, making them excellent models for studying how animals are impacted by changing temperatures. As research on this group of organisms accelerates, it is essential to maintain consistent and optimal methodology so that results can be compared across groups and over time. This review addresses the utility of reptiles and amphibians as model organisms for thermal studies by reviewing the best practices for research on their thermal ecology and physiology, and by highlighting key studies that have advanced the field with new and improved methods. We end by presenting several areas where reptiles and amphibians show great promise for further advancing our understanding of how temperature relations between organisms and their environments are impacted by global climate change. Abstract : Research on the thermal ecology of reptiles and amphibians has facilitated hypothesis testing about how climate change will impact biodiversity. This review article discusses the best practices in thermal research to help unite research toward the common goal of better understanding how temperature impacts organisms. Highlights: we provide a useful "how to" guide for studying the thermal ecology of reptiles and amphibians. We highlight key studies on reptiles and amphibians that help us understand the impacts of the climate crisis on biodiversity.